A review of aerodynamic and wake characteristics of floating offshore wind turbines. (April 2023) - Wang, Xinbao; Cai, Chang; Cai, Shang-Gui; Wang, Tengyuan; Wang, Zekun; Song, Juanjuan; Rong, Xiaomin; Li, Qing'an
Abstract: Wind-generated electricity has effectively promoted the net-zero carbon emission plan, and gradually developed to the deeper ocean, which leads to the emergence of rotating equipment with both rigidity and flexibility: floating offshore wind turbines (FOWT). This review presents crucial determinants for the FOWT's power generation, namely aerodynamics and wakes, which are strongly coupled to the hydrodynamics of the floating platform. The selection of different platforms leads to unique performances, and technology and cost are direct constraints for global floating projects. In the experimental study, the scale model based on some similarity criteria is used to reflect aerodynamic characteristics of the prototype under the multi-degree of freedom motions, but with the contradiction between the Froude number and Reynolds number. Wave basin and wind tunnel are two typical research forms, but the premise is the model scaling to obtain similar dynamic thrust and power. Besides, a cyclic pitch control method is discussed, which is expected to effectively reduce the fatigue load of the spindle and gears. As for the numerical simulation, Blade Element Momentum, Computational Fluid Dynamics, Free-Vortex Wake and Boundary Element behave in different calculation capacities and costs. The power, thrust and wake are obtained under specific platform and motion conditions, and the calculation results lack comparisons and verifications. It is necessary to ignore the extremely limited power increase caused by pitch and surge motion in the design process, to make the platform more stable for dynamic performances and significantly reduce fatigue loads. As a review article, this paper could provide a meaningful reference for those engaged in the aerodynamics of FOWT. Highlights: The factors limiting FOWT's developments are technology and cost. Dynamic similarity should be considered in model scaling and similarity criterion. Pitch and surge motion will increase the average power and its fluctuation. The relative velocity should be used in aerodynamic coefficient calculations. Cyclic pitch control is considered to be useful in aerodynamic load reductions.